Pacing strategy, muscle fatigue, and Technique in 1500-m Speed-Skating and Cycling Time Trials - Stoter, I. K.; MacIntosh, B. R.; Fletcher, J. R.; Pootz, S.; Zijdewind, I.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To evaluate pacing behavior and peripheral and central contributions to muscle fatigue in 1500-m speed-skating and cycling time trials when a faster or slower start is instructed.